RADIASI SINAR ULTRA VIOLET STRAIN ASPERGILLUS ORYZAE UNTUK MENINGKATKAN PRODUKSI ALFA AMILASE - Yetti M.lskandar; Linar Z. Udin; A. T. Karossi (Research Center for Chemistry - LIPI, 1995)
Mutation of Aspergillus oryzae was carried out by ultra violet irradiation at 254 nm. The mutans obtained with 0, 10, 20,30, 40 and 50 minutes irradiation were screened for their amylolytic activity and alpha amylase production. The latter was carried out by aerobic fermentation using sago (Metroxylon spy starch in shake flasks for five days at 30°C with orbital shake at 120 rpm. The observation indicated that the mutant resulted from 10 minute irradiation demonstrated a maximum alpha amylase activity of 1675 Unit/g protein at day-d. The amylase activity was assayed at 40°C for 30 minute incubation. The starch utilization was 87% and 3.84 g dry weight of biomass per L medium was produced. The specific activity of alpha amylase obtained from untreated parental strain was 1069 Unitlg protein. Starch consumption and biomass production was 80% and 3.62 g dry weight/ L medium, respectively. The increase of alpha amylase specific activity at 10 minute irradiation time was 56%.